Design and additive manufacturing of optimized electrodes for energy storage applications. (5th March 2023) - Reale Batista, Mariana Desireé; Chandrasekaran, Swetha; Moran, Bryan D.; Salazar de Troya, Miguel; Pinongcos, Anica; Wang, Zhen; Hensleigh, Ryan; Carleton, Adam; Zeng, Manhao; Roy, Thomas; Lin, Dun; Xue, Xinzhe; et al.
Abstract: Supercapacitors exhibit fast charging/discharging ability and have attracted considerable attention within the automotive, aerospace, and telecommunication industries. Porous carbons, prized for their high electrical conductivity and high surface area, have been attractive candidates for supercapacitor electrodes. Moving to thick electrodes is one strategy to further increase energy density due to a higher volume fraction of active material. However, thick electrodes suffer from sluggish charged species transport, which is why thin electrodes are currently favored. In this work, we investigate the use of computational optimization and additive manufacturing to design and fabricate thick porous electrodes with improved performance. Electrode performance was maximized by designing their morphologies via topology optimization and printing by projection micro stereolithography (PμSL) using commercial resin (PR48). The PR48 resin was then pyrolyzed (PR48-P) to create the final conductive electrode. The optimized PR48-P electrodes exhibited 99% improvement in capacitance compared to control electrodes printed with cubic lattice morphologies. To further improve performance, we formulated a resin combining graphene oxide (GO) and trimethylolpropane triacrylate (TMPTA). Electrodes printed with 3 wt% GO in TMPTA exhibited improved capacitance retention after pyrolysis compared to the PR48-P electrodes. This work demonstrates the benefits of using topology optimization to design electrodes and material development to improve functional properties of 3D printable electrodes. Graphical abstract: Image 1 Highlights: 3D printing of complex shaped electrodes by projection micro stereolithography. Topology optimization is used to design porous electrodes with optimal energy density. Adding graphene oxide into photocurable resin improves the capacitance retention of supercapacitors.